2002
DOI: 10.1177/107110070202301006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Following Anatomic Restoration of Tarsal-Metatarsal Fracture Dislocation

Abstract: Anatomic restoration of displaced fracture-dislocation of the tarsometatarsal junction of the foot is essential, as even "minor" disruptions of this joint complex leads to poor clinical results. In order to determine a "key" element associated with good or poor functional outcomes, 11 patients with excellent radiographic results following surgical treatment of unilateral closed Lisfranc fracture-dislocation of the tarsometatarsal joint of the foot were evaluated at an average of 41.2 (range, 14 to 53) months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 9 publications
(9 reference statements)
1
103
3
3
Order By: Relevance
“…Their diagnosis can be difficult and when missed, patients have poor reported outcomes [2]. Anatomic reduction has been shown to be the primary determining factor in achieving acceptable outcomes [27]. How to best achieve this result remains debatable [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their diagnosis can be difficult and when missed, patients have poor reported outcomes [2]. Anatomic reduction has been shown to be the primary determining factor in achieving acceptable outcomes [27]. How to best achieve this result remains debatable [19].…”
Section: Discussionmentioning
confidence: 99%
“…This is a relatively rare injury with an incidence of approximately 0.2% of all fractures [1] although it is frequently diagnosed late and this leads to poor functional outcomes for the patient [5]. It has been demonstrated that anatomic reduction and rigid stabilization of the Lisfranc complex is the standard of care for these injuries [27]. Open reduction and internal fixation (ORIF) and primary arthrodesis have both been evaluated as treatment options with acceptable results [18].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 11 papers satisfied the inclusion criteria and received critical analysis [2,11,17,21,23,30,31,33,34,38,39]. There were seven case series retrospective studies [2,17,30,31,33,38,39], two comparative cohort studies [23,34], and two prospective randomised control trials-comparative studies [11,21]. From the latter four studies only the data from the groups of patients who were treated by internal fixation were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Gaweda [11] reported, in his series of 41 patients with acute and chronic Lisfranc injuries followed for 16 years, that the best results were achieved after closed reduction and percutaneous K-wire fixation in acute cases. Teng et al [12] analyzed the gait of the injured foot and the control foot in cases of Lisfranc injury with anatomic reduction, and showed no significant difference in the parameters. Therefore, anatomic reduction of the Lisfranc injury is essential to restore normal function of the foot.…”
Section: Discussionmentioning
confidence: 99%